Life cycle and ovipositional preference of Bactrocera carambolae feeding on starfruits - Nur Amirah, Abdul Latif (Universiti Malaysia Sarawak, UNIMAS, 2013)
Malaysia is the main starfruit exporter for Hong Kong, Europe and Singapore market. Hence, starfruit contributes financially to Malaysian economics. But due to the presence of its enemies, Bactrocera carambolae, this species have created havoc in horticulture industries which lead to financial loss. This study focuses more on life history of B. carambolae that are need to be determine before any management control takes place. Generally, life cycle of fruit fly indicated six development stages: mating, oviposition, egg, larvae, pupae and adults while the larval have three development stages (1st, 2nd and 3rd instar). Techniques used in life cycle study involve: fruit fly sampling, fruit fly rearing, egg collection, inoculation, hatchability percentage, disinfestation, pupa collection and the emergence of adults. Eggs of B. carambolae took about 2 days to develop into larva. Larval stage took 6 days to complete and develop into pupa. Then, teneral adults were emerge (26 days) from pupa and will undergo 2-3 weeks of pre-oviposition period before they were fully matured. Regarding experiment 2, investigations were carried out to identify susceptibility of different maturity stage of starfruit to adult females of B. carambolae. B. carambolae species did not infest Index 1 of starfruit while Index 2 was slightly attacked. Fruits from Index 3, Index 4 and Index 5 showed significantly higher infestations than starfruit of Index 2. Among ripe starfruits, Index 5 was more attractive to B. carambolae than fruits that from Index 6 and Index 7. As starfruits ripens, it become more susceptible to B. carambolae attacked.